2015
DOI: 10.1039/c5ce01322d
|View full text |Cite
|
Sign up to set email alerts
|

Polynuclear and polymeric squarato-bridged coordination compounds

Abstract: The coordination properties of 3,4-dihydroxycyclobut-3-ene-1,2-dionate, C 4 O 4 2− (squarate dianion) ligand, in relation to its ability to form different bonding bridging modes with metal ions are explored. These bonding modes led to the formation of a wide range of polynuclear and polymeric coordination compounds. The magnetic properties of the structurally characterized bridged-squarato compounds with CuIJII) and NiIJII) are reported as a function of the structural parameters of the complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 173 publications
5
21
0
Order By: Relevance
“…The carbon‐carbon bond lengths in the four‐membered ring range from 1.450(8) to 1.462(6) Å, falling between the typical values of 1.54 and 1.34 Å assigned to carbon‐carbon single and double bonds, respectively. Similar values are also commonly found in compounds containing the squarate dianion (C 4 O 4 2− ) [36] . Finally, the tribromide counterions exhibit strictly linear geometries, i. e. Br1−Br2−Br3=178.29(3)° and Br4−Br5−Br6=179.11(3)°, with typical Br−Br distances of Br1−Br2=2.5764(9) Å, Br2−Br3=2.5284(9) Å, Br4−Br5=2.5535(9) Å, Br5−Br6=2.5534(9) Å [34] .…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…The carbon‐carbon bond lengths in the four‐membered ring range from 1.450(8) to 1.462(6) Å, falling between the typical values of 1.54 and 1.34 Å assigned to carbon‐carbon single and double bonds, respectively. Similar values are also commonly found in compounds containing the squarate dianion (C 4 O 4 2− ) [36] . Finally, the tribromide counterions exhibit strictly linear geometries, i. e. Br1−Br2−Br3=178.29(3)° and Br4−Br5−Br6=179.11(3)°, with typical Br−Br distances of Br1−Br2=2.5764(9) Å, Br2−Br3=2.5284(9) Å, Br4−Br5=2.5535(9) Å, Br5−Br6=2.5534(9) Å [34] .…”
Section: Resultssupporting
confidence: 82%
“…Similar values are also commonly found in compounds containing the squarate dianion (C 4 O 4 2À ). [36] Finally, the tribromide counterions exhibit strictly linear geometries, i. e. Br1À Br2À Br3 = 178.29(3)°and Br4À Br5À Br6 = 179.11(3)°, with typical BrÀ Br distances of Br1À Br2 = 2.5764(9) Å, Br2À Br3 = 2.5284(9) Å, Br4À Br5 = 2.5535(9) Å, Br5À Br6 = 2.5534(9) Å. [34] In the crystal structure, the cations and anions form alternating layers with each Br 3 À ion making short contacts of approximately 3.5 Å to the C 4 ring of one dication, which is just slightly below the sum of the crystallographic van der Waals radii (3.6 Å).…”
Section: Synthesis and Characterization Of Dimorpholinoacetylene And ...mentioning
confidence: 99%
“…[11][12][13][14][15] The characteristic features of these materials are the exceptional electrical and optical properties . [16][17][18][19][20][21][22][23] Moreover, a large number of studies showed that postsynthetic functionalization or direct syntheses with ligands having suitable functionality can impart hydrogen bond capabilities to the organic-inorganic hybrid. 24,25 Besides, one of the most widely studied functional groups that have been used to impart hydrogen bonding capabilities to the hybrid is the amino, carbonyl, anhydride, cyano group, etc., [26][27][28][29][30] Even more recently, the self-assembly processes are sensitive to diverse synthetic conditions in some cases, change of reaction conditions such as the solvent, pH and temperature for a given set of organic ligands and metal ions can cause various supramolecular architectures.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to this bridging ability, sq has recently been used as a building block in metal-organic frameworks with various functionalities [5][6][7][8][9]. Transition metal sq salts are often subjected to studies on exchange-coupled magnetic materials, as exemplified with Ni 2+ and Cu 2+ salts [10]. Lanthanide (Ln) sq complexes have also been well-known and studied since the 1970s [11,12], thanks to the Ln-O affinity.…”
Section: Introductionmentioning
confidence: 99%